Najskuteczniejszy polski tłumacz pism św. Jana Chryzostoma (Komentarze do Corpus Paulinum) - Longosz, Stanisław (Vox Patrum, 2025)
A review of published translations of the writings of John Chrysostom by Rev. Prof. Antoni Paciorek.